Vitamin D ameliorates age-induced nonalcoholic fatty liver disease by increasing the mitochondrial contact site and cristae organizing system (MICOS) 60 level - Gyu Hee Kim; Hyeon-Ju Jeong; Yoo Jeong Lee; Hyeon Young Park; Soo Kyung Koo; Joo Hyun Lim (Experimental and Molecular Medicine, 2024)
Abstract Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease. Despite intensive research, considerable information on NAFLD development remains elusive. In this study, we examined the effects of vitamin D on age-induced NAFLD, especially in connection with mitochondrial abnormalities. We observed the prevention of NAFLD in 22-month-old C57BL/6 mice fed a vitamin D3-supplemented (20,000 IU/kg) diet compared with mice fed a control (1000 IU/kg) diet. We evaluated whether vitamin D3 supplementation enhanced mitochondrial functions. We found that the level of mitochondrial contact site and cristae organizing system (MICOS) 60 (Mic60) level was reduced in aged mice, and this reduction was specifically restored by vitamin D3. In addition, depletion of Immt, the human gene encoding the Mic60 protein, induced changes in gene expression patterns that led to fat accumulation in both HepG2 and primary hepatocytes, and these alterations were effectively prevented by vitamin D3. In addition, silencing of the vitamin D receptor (VDR) decreased the Mic60 levels, which were recovered by vitamin D treatment. To assess whether VDR directly regulates Mic60 levels, we performed chromatin immunoprecipitation and reporter gene analysis. We discovered that VDR directly binds to the Immt 5’ promoter region spanning positions −3157 to −2323 and thereby upregulates Mic60. Our study provides the first demonstration that a reduction in Mic60 levels due to aging may be one of the mechanisms underlying the development of aging-associated NAFLD. In addition, vitamin D3 could positively regulate Mic60 expression, and this may be one of the important mechanisms by which vitamin D could ameliorate age-induced NAFLD.